Use of prescription opioids and other psychotropic drugs during pregnancy and their impact on the mother and developing child: protocol for a cohort study using linked administrative data from Manitoba and British Columbia, Canada - Lauren E Kelly; Kimberlyn McGrail; Jennifer E Enns; Dan Chateau; Alan Katz; Marni Brownell; Jason Kim; Deepa Singal; Ana Hanlon-Dearman; Lindsey Dahl; Nathan C Nickel; Colin Dormuth; et al. (BMJ Open)
Introduction Opioids are prescribed to manage pain. Approximately 1 in 20 pregnant women in Canada are prescribed opioids during the prenatal period, which may occur concurrently with other psychotropic drug use. The health implications of the independent and concurrent prenatal use of these drugs are not fully understood; however, adverse neonatal and longer-term outcomes have been suggested. This protocol describes a study to update the epidemiology of prenatal exposure to opioid and other psychotropic drug use during pregnancy, providing an enhanced understanding of the potential impacts on the mother and child to help inform decisions regarding prescription and use.Methods and analysis The retrospective cohort study design uses population-based administrative data from Manitoba and British Columbia, Canada, to investigate the effect of prenatal opioid and concurrent psychotropic drug use on maternal and child outcomes. All mother–child dyads from 2000/2001 to 2019/2020 (approximately 1M pairs) will be identified and assigned to exposure groups based on the number of opioid and other psychotropic drug dispensations to the mother during the prenatal period. Maternal sociodemographic characteristics, prescribing patterns, short- and long-term child health and education outcomes and maternal outcomes will be examined.Ethics and dissemination The study was approved by the University of Manitoba Human Research Ethics Board (No. HS24397 – H2020:470) and the University of British Columbia Clinical Research Ethics Board (No. H21-02262). The study will generate findings that will add to the growing body of evidence of potential short- and long-term adverse effects on children exposed to these drugs prenatally and will help to inform safe prescribing guidelines during pregnancy. Results will be published in peer-reviewed journals.